2010
DOI: 10.1111/j.1749-6632.2009.05084.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms in evolutionary cardiology failure

Abstract: Integration of the relevant evolutionary paradigm in cardiology has not yet been fully achieved: In the past, heart failure (HF) was mainly ascribed to infections, and the origins of cardiac hypertrophy (CH) were regarded as mechanical. Recent changes in lifestyle have both reduced the incidence of infections and increased lifespan, and HF is now seen as a complex disease--one that is still caused by mechanical disorder, but also associated with ischemia and senescence. The long-held view that CH serves to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The failing cardiac phenotype is characterized by a shift toward a more "fetal" expression profile, encompassing increases in expression of fetal structural and contractile protein isoforms, and preferential use of glucose and lactate as energy sources over fatty acids (21). This expression profile is similar to that observed in RNCM.…”
Section: Discussionsupporting
confidence: 55%
“…The failing cardiac phenotype is characterized by a shift toward a more "fetal" expression profile, encompassing increases in expression of fetal structural and contractile protein isoforms, and preferential use of glucose and lactate as energy sources over fatty acids (21). This expression profile is similar to that observed in RNCM.…”
Section: Discussionsupporting
confidence: 55%
“…Thermodynamic data have suggested that this reduction is due to a decreased recruitment of myosin crossbridges. Whereas the diminution of V max is a beneficial event at the cardiomyocyte level, allowing the cardiac fiber to contract at a normal energy cost, at the LV level the diminution of V max is the first step that will finally lead to dysfunction/failure [12].…”
Section: Response Of the Cardiomyocyte To Pressure Overloadmentioning
confidence: 99%
“…An integral nodal point during the development of heart failure is cardiac hypertrophy. 5,6 Cardiac hypertrophy is heritable 7 and is a recognized risk factor for heart failure. 8,9 In this study, we hypothesized that interindividual variability in the genetic risk factors for the hypertrophy trait may also influence the risk for developing heart failure or its prognosis over time.…”
Section: Introductionmentioning
confidence: 99%